Cloning of araA Gene Encoding L-Arabinose Isomerase from Marine Geobacillus stearothermophilus Isolated from Tanjung Api, Poso, Indonesia - DEWI FITRIANI; BUDI SAKSONO (HAYATI Journal of Biosciences, 2010)
L-arabinose isomerase is an enzyme converting D-galactose to D-tagatose. D-tagatose is a potential sweetener-sucrose substitute which has low calorie. This research was to clone and sequence araA gene from marine bacterial strain Geobacillus stearothermophilus isolated from Tanjung Api Poso Indonesia. The amplified araA gene consisted of 1494 bp nucleotides encoding 497 amino acids. DNA alignment analysis showed that the gene had high homology with that of G. stearothermophilus T6. The enzyme had optimum activity at high temperature and alkalin condition.